Effects Of Restructuring Of Electricity Supply Industry In Malaysia On Tenaga Nasional Berhad - Abdul Rahman, Mohd Radzian (2005)
TNB was restructured to a few private limited companies which are TNB Generation Sdn. Bhd., TNB transmission sdn. Bhd. and TNB Distribution sdn. BHd. The past restructuring of the electricity supply industry may has affected TNB operational expenses and reduce net profit after tax. Ahead, further restructuring and deregulation in Malaysia's electricity supply industry is still in the thought of many people.